Living in Parallel Universes: Physiotherapists and Insurance Workers’ Beliefs in the West Australian Workers’ Compensation System - Beales, Darren; Ruscoe, G. (2013)
Objective: This study investigated beliefs related to ‘grey areas’ of in- jured worker management in the West Australian workers’ compen- sation system. Methods: Six common scenarios related directly to the management of injured workers were devised with two main themes of ‘Reason- able Expenses’ and ‘Health Worker Roles’. The scenarios were fo- cused on musculoskeletal disorders. Eighty physiotherapists and 48 insurance workers (case managers, injury management advisors) par- ticipated in an online questionnaire. Level of agreement with each scenario was assessed and opportunity provided for individual com- ments. Results: Differences were identified in the beliefs related to the six scenarios both between and within professions. Both professions had varied opinions as to when treatment under the workers’ com- pensation system should cease. There was a lack of consensus in both professions on the provision of treatment for comorbidity within the system. There were differing opinions between professions re- lated to the role of various stakeholders, with good communication emerging as a common theme to deal with potential role conflicts. Conclusion: This study confirms the existence of a number of ‘grey areas’ directly related to injured worker management in the Western Australian workers’ compensation system. These ‘grey areas’ have the potential to result in inefficiencies, inconsistency in care, confu- sion and frustration for stakeholders.